Pengaruh Financial Literacy, Parental Financial Behavior Dan Herding Behavior Terhadap Keputusan Investasi Saham - Annisa Novita Sari; Rina Susanti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyse the influence of financial literacy, parental financial behaviour, and herding behaviour on stock investment decisions among students at the Faculty of Economics and Business, Slamet Riyadi University, Surakarta. Using a quantitative approach, primary data was collected through a questionnaire distributed to 100 respondents selected using purposive sampling techniques. Data analysis was conducted comprehensively through descriptive analysis, multiple linear regression, and hypothesis testing using t-tests, F-tests, and the coefficient of determination ($R^2$). The t-test results showed that the three independent variables partially had a significant effect on stock investment decisions, as evidenced by the p-values obtained for financial literacy (0.000), parental financial behaviour (0.000), and herding behaviour (0.002), all of which were below the significance level of 0.05